REACTION OF LANDSCAPES OF THE NORTH CAUCASUS ON THE CURRENT CLIMATIC CHANGES - Z. V. Atayev; V. V. Bratkov (Юг России: экология, развитие)
The authors analyze the climatic conditions in the landscapes of the Northern Caucasus during the period of 1966–2010 in comparison with the previous base period (1931–1960). It is noted general increase of the air temperature (from 0.2 to 0.7°) and the rainfall (30–65 mm) as well. Despite of this fact the value of the humidity factor being the integral index of the inner landscape moisturizing conditions changed very slightly (not more than by 0.10). The overall climate changes were revealed not in the form of the unidirectional sustainable trends, but through the significant 2–3 year fluctuations in the temperature and precipitations. As a result the temporary landscape structure has not undergone any significant changes. It allows concluding the stability of the landscape structure of the region.